Sustainable urban drainage systems in established city developments: Modelling the potential for CSO reduction and river impact mitigation. (15th November 2020) - Riechel, Mathias; Matzinger, Andreas; Pallasch, Matthias; Joswig, Kay; Pawlowsky-Reusing, Erika; Hinkelmann, Reinhard; Rouault, Pascale
Abstract: Sustainable urban drainage systems (SUDS) can significantly reduce runoff from urban areas. However, their potential to mitigate acute river impacts of combined sewer overflows (CSO) is largely unknown. To close this gap, a novel coupled model approach was deployed that simulates the effect of realistic SUDS strategies, developed for an established city quarter, on acute oxygen depressions in the receiving river. Results show that for an average rainfall year the SUDS strategies reduce total runoff by 28%–39% and peak runoff by 31%–48%. Resulting relative reduction in total CSO volume ranges from 45%–58%, exceeding annual runoff reduction from SUDS by a factor of 1.5. Negative impacts in the form of fish-critical dissolved oxygen (DO) conditions in the receiving river (<2 mg DO L −1 ) can be completely prevented with the SUDS strategies for an average rainfall year. The realistic SUDS strategies were compared with a simpler simulation approach which consists in globally downscaling runoff from all impervious areas. It indicates that such a simple approach does not completely account for the positive effect of SUDS, underestimating CSO volumes for specific rain events by up to 13%. Accordingly, global downscaling is only recommended for preliminary planning purposes. Highlights: The developed modelling approach can simulate city-wide river impacts of SUDS. Acute oxygen depressions in the river can be prevented with SUDS strategies. Relative reduction of CSO volume generally exceeds relative runoff reduction. Runoff peak attenuation is a relevant factor for CSO reduction and impact mitigation.